On the semantic history of selected terms of endearment - Agnieszka Grząśko (LingBaW)
The present paper attempts to discuss the semantic history of a handful of terms of endearment (aka pet names, sweet talk, affectionate talk, soft words, terms of affection or sweet words) and the role of the cognitive mechanisms in the changes of their meaning. We focus the reader’s attention on a few lexical items which represent such mechanisms as foodsemy (e.g. honey, sugar), which seems to be one of the most prolific ones, plantosemy (pumpkin) or zoosemy (pet). Furthermore, we trace the semantic development of terms which from the beginning of their existence have been employed as pet names (sweetheart), words which are no longer endearments, because they underwent the process of meaning amelioration or pejoration (mopsy, bully) and – last but not least – nouns whose semantic shift is based on the pattern (POSITIVE) EMOTIONS → ENDEARMENTS (joy).